PENGARUH KARAKTERISTIK PEMDA TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN DIWEBSITE PEMDA (STUDI EMPERIS PADA PEMERINTAH DAERAH SEMALANG RAYA PERIODE 2013-2015) - Hastini Yanti Susiyah; Afifudin Afifudin; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2017)
The purpose of this research is to analyze the influence of local government characteristics on the level of financial statement disclosure on thelocal government website (empirical study on local government entire of Malang). The data used in this study is secondary data obtained from the website of local government and regional statistics center. The sample used in this research is 6 LKPD Regency and City  all of entire Malang on  2013-2015. The results of this study indicate that the size and wealth of local governments and Number of Population does not significantly influence LKPD Disclosure Rate on the website.